Internet use by middle-aged and older adults: Longitudinal relationships with functional ability, social support, and self-perceptions of aging - Mariano, J.; Marques, S.; Ramos, M. R.; De Vries, H. (Psychology and Aging, 2021)
In an increasingly digital world, those who remain offline may face greater challenges across multiple contexts of everyday life. Besides being less likely to be internet users, older age groups go online less frequently and for fewer activities. Understanding which factors facilitate or prevent internet use in later life is therefore essential to minimize existing age-based digital inequalities. Based on the 2014 and 2017 waves of the German Ageing Survey, comprising 3,479 respondents aged 40 years and older, this study examined the longitudinal relationships of a wide range of often overlooked, yet potentially relevant factors related to functional ability, social support, and self-perceptions of aging with general internet use and seven specific online behaviors. As the only factors relating to general use and a considerable number of specific uses, cognitive functioning and competence-related self-perceptions of aging emerged as the most important correlates of internet use in middle and late adulthood. Better cognitive functioning preceded contacting friends, acquaintances, and relatives, searching for information, banking, and shopping more frequently 3 years later. In turn, competence self-perceptions of aging preceded contacting others, searching for new social contacts, seeking information, banking, engaging in online entertainment, and creating contents more frequently 3 years later. Reciprocal relationships were also found between each factor and general use, suggesting mutual influences. Additionally, physical functioning and received informational support preceded greater use for specific activities. These findings elucidate which factors to consider when developing effective strategies to promote general and specific internet use among middle-aged and older adults.